Use of Recycled Concrete Aggregates in Production of Green Cement-Based Concrete Composites: A Review - Natt Makul (Crystals, 2021)
Recycled concrete aggregates (RCA) are used in existing green building composites to promote the environmental preservation of natural coarse aggregates (NCA). Besides, the use of RCA leads to potential solutions to the social and economic problems caused by concrete waste. It is found that insufficient information on the longevity and sustainability of RCA production is a serious issue that requires close attention due to its impact on changing aspects of the sector. However, more attention has been paid to explaining the effect of RCA on concrete durability, as well as the properties of fresh and hardened concrete. Therefore, this study aims to provide a critical review on the RCAs for the production of high-performances concrete structures. It begins by reviewing the source, originality, types, prediction of service life, features and properties of RCA, as well as the effect of RCA on concrete performance. In addition, this literature review summarizes the research findings to produce complete insights into the potential applications of RCA as raw, renewable, and sustainable building materials for producing greener concrete composite towards industrializing ecofriendly buildings today. Further, it has also highlighted the differences in the current state of knowledge between RCAs and NCAs, and offers several future research suggestions. Through this critical and analytical study, it can be said that RCA has the possible use in the production of high-performance structural concrete depending on the source and type of recycled aggregate while the RCA can be used widely and safely to produce traditional green concrete.